2016
DOI: 10.18632/oncotarget.13584
|View full text |Cite
|
Sign up to set email alerts
|

The change of HCN1/HCN2 mRNA expression in peripheral nerve after chronic constriction injury induced neuropathy followed by pulsed electromagnetic field therapy

Abstract: Neuropathic pain is usually defined as a chronic pain state caused by peripheral or central nerve injury as a result of acute damage or systemic diseases. It remains a difficult disease to treat. Recent studies showed that the frequency of action potentials in nociceptive afferents is affected by the activity of hyperpolarization-activated cyclic nucleotide-gated cation channels (HCN) family. In the current study, we used a neuropathy rat model induced by chronic constriction injury (CCI) of sciatic nerve to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…For example, a downregulation in HCN1 subunit expression (which confer faster kinetics on HCN channel complexes) in iPVINs, coupled with an increased expression of the more slowly conducting HCN4 subunits, could contribute to the reduced excitability seen in these cells after nerve injury [60]. Although changes in HCN subunit expression in distinct dorsal horn neuron populations have yet to be reported following peripheral nerve injury, it has been shown that mRNA for both HCN1 and HCN2 is markedly decreased in dorsal root ganglion neurons following axotomy [145,148]. Should spinal interneurons undergo similar changes, restoring normal HCN subunit expression in these cells could re-establish spinal inhibition and alleviate the mechanical hypersensitivity seen in pathological conditions.…”
Section: Future Directions-novel Targetsmentioning
confidence: 99%
“…For example, a downregulation in HCN1 subunit expression (which confer faster kinetics on HCN channel complexes) in iPVINs, coupled with an increased expression of the more slowly conducting HCN4 subunits, could contribute to the reduced excitability seen in these cells after nerve injury [60]. Although changes in HCN subunit expression in distinct dorsal horn neuron populations have yet to be reported following peripheral nerve injury, it has been shown that mRNA for both HCN1 and HCN2 is markedly decreased in dorsal root ganglion neurons following axotomy [145,148]. Should spinal interneurons undergo similar changes, restoring normal HCN subunit expression in these cells could re-establish spinal inhibition and alleviate the mechanical hypersensitivity seen in pathological conditions.…”
Section: Future Directions-novel Targetsmentioning
confidence: 99%
“…Recent experiments on animals provide hope for the next clinical use of PEMF. Some authors have shown a positive effect of pulsed electromagnetic field (PEMF) on infarct size and inflammation after cerebral ischemia in mice, other have described that PEMF enhances the phosphorylation of protein kinase B (Akt) and endothelial nitric oxide synthase (eNOS), which may be closely related to attenuated cell apoptosis by increasing the releasing of nitric oxide (NO) and other have described change of HCN1 / HCN2 mRNA expression in peripheral nerve after chronic constriction injury and indicated that PEMF can promote nerve regeneration and could be used for the treatment of chronic ischemia [39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…[81] Currently, the expression of HCN channels isoforms is also being investigated with regard to some peripheral nervous system pathologies, such as neuropathic pain. [82] It was found that HCN1 and HCN2 were reduced in the left and right sciatic nerve in a rat neuropathic pain model; [83] however, there was no change in the dorsal root ganglia (DRG), unlike other study findings that did indicated decreased HCN1 and HCN2 in the DRG. [82] In addition to nervous system pathologies, HCN1 also seems to be associated with photoreceptor degeneration.…”
Section: Hcn Channels and Pathophysiologymentioning
confidence: 92%